Prospective pilot study to detect dogs with non food‐induced canine atopic dermatitis using Fourier transform infrared spectroscopy. Issue 5 (8th August 2016) - Bruet, Vincent; Dumon, Henri; Bourdeau, Patrick; Desfontis, Jean‐Claude; Martin, Lucile
Abstract : Background: The diagnosis of canine atopic dermatitis (CAD) remains challenging due to the lack of a simple biomarker or metabolic profile. In human medicine, Fourier transform infrared spectroscopy (FTIR) is an analytical technique used for several diseases. It requires a small amount of sample and allows the identification of structural moieties of biomolecules on the basis of their infrared absorption, with limited sample pretreatment. Hypothesis/Objectives: The aim of the study was to evaluate the diagnostic value of FTIR. Animals: Three groups were tested: 21 dogs with non food‐induced CAD (NFICAD), 16 dogs with inflammatory conditions of various origins but without allergic dermatoses (OD) and 10 healthy dogs (H). Methods: Peripheral blood was collected and spectra were acquired with a FTIR spectrophotometer. A principal component analysis (PCA) was performed on the full wavenumber spectra (4000–600/cm), followed by a Fisher discriminant analysis (DA) to assess the differences between the three groups. Results: The PCA followed by the DA of whole spectra showed significant differences between the three groups. These results suggest that by using the FTIR method, dogs with NFICAD can be differentiated from healthy dogs and dogs with nonallergic inflammation. There was no overlap between the spectral data of the three groups indicating that NFICAD dogs were correctly segregated from the H and OD groups. Conclusions: A study on a larger cohort including common pruritic skin diseases is necessary to confirm these initial results and the relevance of this diagnostic technique. Abstract : Background – The diagnosis of canine atopic dermatitis (CAD) remains challenging due to the lack of a simple biomarker or metabolic profile. In human medicine, Fourier transform infrared spectroscopy (FTIR) is an analytical technique used for several diseases. It requires a small amount of sample and allows the identification of structural moieties of biomolecules on the basis of their infrared absorption, with limited sample pretreatment. Hypothesis/Objectives – The aim of the study was to evaluate the diagnostic value of FTIR. Conclusions – A study on a larger cohort including common pruritic skin diseases is necessary to confirm these initial results and the relevance of this diagnostic technique. Résumé: Contexte: Le diagnostic de dermatite atopique canine (DAC) reste un défi en raison du manque d'un simple biomarqueur ou d'un profil métabolique. En médecine humaine, la FTIR (Fourier transform infrared spectroscopy) est une technique analytique utilisée pour différentes maladies. Elle nécessite une petite quantité d'échantillon et permet une identification de la structure des fragments de biomolécules sur la base de leur absorption infra‐rouge avec un prétraitement limité des échantillons. Hypothèses/Objectifs: Le but de cette étude était d'évaluer la valeur diagnostique de FTIR. Sujets: Trois groupes ont été testés: 21 chiens avec DAC non induite par l'aliment (NFICAD), 16 chiens avec atteinte inflammatoire de différentes origines mais sans dermatoses allergiques (OD) et 10 chiens sains (H). Méthodes: Le sang périphérique a été collecté et des spectres ont été acquis avec spectromètre FTIR. Un PCA (principal component analysis) a été réalisé sur spectre total (4000–600/cm −1 ), suivi d'un test de Fischer d'analyse discriminante (DA) afin d'évaluer les différences entre les trois groupes. Résultats: Les trois groupes ont montrés des différences significatives. Ces résultats suggèrent qu'à l'aide du FTIR, les chiens avec NFICAD peuvent être distingués des chiens sains et des chiens atteints d'inflammation non allergique. Il n'y avait aucun chevauchement entre les spectres des trois groupes indiquant que les chiens NFICAD étaient correctement distingués des groupes H et OD. Conclusions: Une étude sur une cohorte plus large comprenant des dermatoses prurigineuses fréquentes est nécessaire pour confirmer ces données initiales et la pertinence de cette technique diagnostique. Resumen: Introducción: El diagnóstico de dermatitis atópica canina (CAD) sigue siendo un reto debido a la falta de un biomarcador simple o un perfil metabólico. En medicina humana, la espectroscopía infrarroja transformada según Fourier (FTIR) es una técnica analítica utilizada para varias enfermedades. Se requiere una pequeña cantidad de muestra y permite la identificación de restos estructurales de biomoléculas sobre la base de su absorción en el infrarrojo, con pretratamiento de la muestra limitado. Hipótesis/Objetivos: El objetivo del estudio fue evaluar el valor diagnóstico de FTIR. Animales: Se probaron tres grupos: 21 perros con enfermedad alérgica no alimentaria (NFICAD), 16 perros con enfermedades inflamatorias de origen diverso, pero sin dermatosis alérgicas (OD) y 10 perros sanos (H). Métodos: se obtuvo sangre periférica y los espectros fueron realizados con un espectrofotómetro FTIR. Un análisis de componentes principales (PCA) se realizó en los espectros completos (4000–600/cm −1 ), seguido de un análisis discriminante de Fisher (DA) para evaluar las diferencias entre los tres grupos. Resultados: El PCA seguido de la DA de los espectros completos mostraron diferencias significativas entre los tres grupos. Estos resultados sugieren que al utilizar el método FTIR, los perros con NFICAD pueden diferenciarse de los perros sanos y perros con la inflamación alérgica. No hubo superposición entre los datos espectrales de los tres grupos indicando que los perros con NFICAD fueron correctamente separados de los grupos H y OD. Conclusiones: Se necesita un estudio sobre una población de animales más amplia, incluyendo enfermedades comunes pruriginosas, para confirmar estos resultados iniciales y la relevancia de esta técnica de diagnóstico. Zusammenfassung: Hintergrund: Die Diagnose der atopischen Dermatitis (CAD) des Hundes bleibt aufgrund fehlender einfacher Biomarker oder eines metabolischen Profils eine Herausforderung. In der Humanmedizin ist die Fourier‐Transform‐Infrarotspektroskopie (FTIR) eine analytische Technik, die bei verschiedenen Krankheiten angewendet wird. Sie benötigt eine kleine Probenmenge und erlaubt eine Identifizierung der strukturellen Teile von Biomolekülen auf der Basis der Infrarotabsorption, bei limitierter Vorbehandlung der Proben. Hypothese/Ziele: Das Ziel dieser Studie war eine Evaluierung des diagnostischen Wertes der FTIR. Tiere: Es wurden drei Gruppen getestet: 21 Hunde mit nicht durch Futter induzierter CAD (NFICAD), 16 Hunde mit entzündlichen Zuständen unterschiedlichster Ursache aber ohne allergischen Dermatosen (OD) und 10 gesunde Hunde (H). Methoden: Es wurde peripheres Blut entnommen und die Spectra mittels FTIR Spektrophotometer gewonnen. Eine Hauptkomponentenanalyse (PCA) wurde an den Gesamtspectra durchgeführt (4000–600/cm −1 ), gefolgt von einer Diskriminanzanalyse nach Fisher (DA), um die Unterschiede der drei Gruppen festzustellen. Ergebnisse: Die PCA, gefolgt von der DA der Gesamtspectra zeigte signifikante Unterschiede zwischen den drei Gruppen. Diese Ergebnisse weisen darauf hin, dass mit der FTIR Methode Hunde mit NFICAD von gesunden Hunden und von Hunden mit nichtallergischer Entzündung unterschieden werden können. Es bestand keine Überlappung zwischen den Spektraldaten der drei Gruppen, was darauf hinweist, dass NFICAD Hunde korrekt von den H und OD Gruppen isoliert wurden. Schlussfolgerungen: Eine Studie mit einer größeren Studiengruppe mit häufigen juckenden Erkrankungen ist nötig, um diese anfänglichen Ergebnisse und die Relevanz dieser Diagnosetechnik zu bestätigen. 要約: 背景: 犬のアトピー性皮膚炎(CAD)の診断には、簡単なバイオマーカーや代謝プロファイルが存在せず、いまだに困難である。人医療域では、フーリエ変換赤外線分光分析(Fourier transform infrared spectroscopy; FTIR)が様々な疾患の診断に用いられている。検査には少量のサンプルとわずかな前処置のみが必要で、赤外線吸収能に基づいて生体分子の構造部位を同定することができる。 仮説/目的: 本研究の目的は、FTIRの診断的価値を評価することである。 供与動物: 非食物誘発性CAD(NFICAD)の犬21頭、アレルギー性皮膚疾患以外の様々な臓器の炎症性疾患(OD)の犬16頭、健康犬(H)10頭の3群について検査した。 方法: 末梢血を採取し、FTIR分光光度計を用いて、周波数範囲を測定した。全周波数範囲(4000‐600/cm ‐1 )にて、主成分分析(PCA)およびフィッシャーの判別分析法(DA)を実施し、3群間の差を比較した。 結果: 全周波数範囲にてDAを実施したPCAにおいて、3群間に有意差が認められた。このことは、FTIR法はNFICADと健康犬および非アレルギー性炎症性疾患を鑑別可能であることを示唆している。これら3群間の周波数範囲データにオーバーラップはなく、NFICAD犬がH群およびOD群から、正確に区分けされたことが示唆された。 結論: 今回の初期成果および本診断法の妥当性を裏付けるためには、一般的な掻痒性皮膚疾患を含むより大規模なコホート研究が必要である。 摘要: 背景: 由于缺乏单个生物标记物或代谢概况, 诊断犬异位性皮炎(CAD)仍是挑战。在人医上, 傅里叶变换红外光谱(FTIR)可用于多种疾病的分析技术。它只需要少量样本, 在红外吸收预处理下, 可以识别有限样本的生物分子结构基团。 假设/目的: 本次研究目的为评估FTIR的诊断意义。 动物: 实验分为三组:21只无食物过敏的CAD患犬(NFICAD), 16只患有多来源炎症但没有过敏性皮肤病(OD)的犬只, 以及10只健康犬(H)。 方法: 采集外周血, 通过FTIR分光光度计检测区光谱。对所有光谱(4000–600/cm –1 )进行主成分分析(PCA), 然后使用费舍尔判别分析(DA)评估三组间的区别。 结果: PCA以及之后的全光谱DA显示三组间差异显著。这结果表明, 使用FTIR方法, NFICAD患犬可与健康犬和非过敏性炎症区分。三组光谱数据没有重叠, 表明NFICAD患犬和H组以及OD组完全不同。 总结: 还需要对更多常见瘙痒性皮肤病患犬进行研究, 来确定本次研究结果, 以及与诊断技术的关联。 Resumo: Contexto: O diagnóstico de dermatite atópica canina (DAC) permanece desafiador devido a ausência de um biomarcador simples ou um perfil metabólico. Na medicina humana, a espectroscopia infravermelha transformada de Fourier (FTIR) é uma técnica analítica utilizada para diversas doenças e requer uma quantidade pequena de amostra. A FTIR permite a identificação de segmentos estruturais de biomoléculas baseado em sua absorção infravermelha, necessitando de preparação limitada da amostra. Hipótese/Objetivos: Este estudo tem como objetivo avaliar o valor diagnóstico da FTIR. Animais: Três grupos foram testados: 21 cães com dermatite atópica não induzida por alimentos (DACNIA); 16 cães com doenças inflamatórias diversas, mas sem dermatopatias alérgicas (OD) e 10 cães saudáveis (S). Métodos: Sangue periférico foi coletado e o espectro foi adquirido por meio de espectrofotômetro de FTIR. A análise componente principal (PCA) foi realizada em espectro completo (400–600/cm 2 ), seguido de análise discriminatória de Fisher (DA) para avaliar as diferenças entre os três grupos. Resultados: A PCA seguida pela DA do espectro total demonstrou diferença significativa entre os três grupos. Os resultados sugerem que através da utilização do método de FTIR, cães com DACNIA podem ser diferenciados de cães saudáveis e de cães com inflamação não alérgica. Não houve sobreposição entre os dados de espectro dos três grupos, indicando que cães com DACNIA foram corretamente segregados dos grupos S e OD. Conclusões: Um estudo com uma coorte mais extensa incluindo doenças pruriginosas corriqueiras é necessário para confirmar estes resultados iniciais e a relevância desta técnica diagnóstica.